Usability evaluation of smartphone gestures in supporting elderly users - Salman, H.M. (Springer, 2019)
The elderly often experience usability problems in using touchscreen gestures to operate smartphones. Compared to adults and children, elderly users are outperformed in executing gestures on smartphone devices. Previous studies have recommended the tap and swipe gesture when designing apps for the elderly while criticising âtap and holdâ, drag, and pinch as overly complex gestures for the elderly. The objective of this study is to evaluate the usability of smartphone gestures in supporting elderly users. Ten elderly participants were recruited in conducting a two-stage experiment. The first stage of this study reassessed the usability of the current tap and swipe. While the second stage investigated the usability of the three criticised gestures against the usability of three alternative gestures proposed in this study. The results of the study affirmed the high usability of the tap and swipe gestures and the three proposed gestures. The study has contributed to providing a better understanding of the usability of gestures in supporting the elderly. Â© Springer Nature Switzerland AG 2019.